Additively Manufactured Dielectric Waveguides for Advanced Concepts for Millimeter-Wave Interconnects - Distler, Felix; Sippel, Mark; Schür, Jan; Gold, Gerald; Helmreich, Klaus; Vossiek, Martin (IEEE Transactions on Microwave Theory and Techniques, 2019)
Technology mega trends, such as autonomous driving, multiple-input multiple-output (MIMO), or multi-gigabit communication, drastically increase the demand for ultra-broadband millimeter-wave (mmW) transmission line technologies. A broadband and robust signal and data transmission between components and modules at low cost is a mandatory requirement to ensure high-performance functionality of advanced communication and radar systems. Dielectric waveguides (DWGs) are a highly suitable technology to meet these requirements due to their outstanding transmission capabilities for mmW signals coupled with their high flexibility, low weight, and low cost. Additive manufacturing (AM) processes based on dielectric materials open up new perspectives for fully automated wiring of mmW modules and systems, and they enable cost-efficient application-specific solutions. In this article, we propose novel printed DWG designs with optimized transmission performance. Measurement results of different DWG designs demonstrate the excellent functionality of the proposed transmission line and interconnection concepts. These results and the shown resiliency and practicality of the presented approaches illustrate attractive opportunities for new interconnect technologies based on new manufacturing processe